Double barreled wet colostomy. Case report and description of the surgical technique - Salgado-Cruz, Luis Enrique; Espin-Basany, Eloy; Chapa-Lobo, Alberto Félix; Rangel-Ríos, Hugo Antonio; Garza-Maldonado, Ana Guadalupe; Ortiz de Elguea-Lizárraga, José I. (Journal of Coloproctology, 2020)
Pelvic exenteration has showed to be beneficial therapeutically and palliatively in locally advanced colorectal cancer. Reconstruction of urinary transit posterior to a cystectomy has always been challenging with many associated complications. We present a 58-year-old male with locally advanced rectal cancer in which a pelvic exenteration and a double-barreled wet colostomy (DBWC) was created for urinary reconstitution. We present the surgical technique of DBWC. DBWC is a good alternative to other urinary reconstructions because fecal and urinary derivation occurs in only one stoma, the stoma output is easier to manage, and fewer complications are seen compared to other urinary reconstructions. Long-term surveillance is mandatory in patients with a DBWC because there is an increased risk of neoplasm in the reservoir.
Keywords: Double barreled wet colostomy; Case report; Surgical technique; Pelvic exenteration; Reconstruction of urinary transit